In vitro evaluation of novel antisense oligonucleotides is predictive of in vivo exon skipping activity for Duchenne muscular dystrophy. - Wang, Q; Yin, H; Camelliti, P; Betts, C; Moulton, H; Lee, H; Saleh, A; Gait, M; Wood, M (2010)
BACKGROUND: Targeted splice modulation of pre-mRNA transcripts by antisense oligonucleotides (AOs) can correct the function of aberrant disease-related genes. Duchenne muscular dystrophy (DMD) arises as a result of mutations that interrupt the open-reading frame in the DMD gene encoding dystrophin such that dystrophin protein is absent, leading to fatal muscle degeneration. AOs have been shown to correct this dystrophin defect via exon skipping to yield functional dystrophin protein in animal models of DMD and also in DMD patients via intramuscular administration. To advance this therapeutic method requires increased exon skipping efficiency via an optimized AO sequence, backbone chemistry and additional modifications, and the improvement of methods for evaluating AO efficacy. METHODS: In the present study, we establish the conditions for rapid in vitro AO screening in H(2)K muscle cells, in which we evaluate the exon skipping properties of a number of known and novel AO chemistries [2'-O-methyl, peptide nucleic acid, phosphorodiamidate morpholino (PMO)] and their peptide-conjugated derivatives and correlate their in vitro and in vivo exon skipping activities. RESULTS: The present study demonstrates that using AO concentrations of 300 nM with analysis at a single time-point of 24 h post-transfection allowed the effective in vitro screening of AO compounds to yield data predictive of in vivo exon skipping efficacy. Peptide-conjugated PMO AOs provided the highest in vitro activity. We also show for the first time that the feasibility of rapid AO screening extends to primary cardiomyocytes. CONCLUSIONS: In vitro screening of different AOs within the same chemical class is a reliable method for predicting the in vivo exon skipping efficiency of AOs for DMD.